Clinical, Surgical and Outcome Predictive Factor Analysis of Operated Acute Subdural Hematoma Cases: A Retrospective Study of 114 Operated Cases at Tertiary Centre - Singh, Rahul; Prasad, Ravi Shankar; Singh, Kulwant; Sahu, Anurag; Pandey, Nityanand (Indian Journal of Neurosurgery, 2021)
Objective To analyze clinical, surgical and outcome predictive factors of operated acute subdural hematoma (SDH) cases for prognostication and surgical outcome prediction.Material and Methods This retrospective study includes 114 patients operated for acute SDH in the Department of Neurosurgery of IMS BHU, Varanasi, India, a tertiary care center, between 1 August 2018 and 1 November 2019. Each patient was evaluated for age, sex, mode of injury, localization of hematoma, clinical presentation, comorbidity, severity of injury, best motor response, CT findings, and Glasgow outcome scale (GOS) at discharge. The outcome was also evaluated by further making a dichotomized group using GOS in death/dependent (1–3) versus independent (4–5). Statistical tests were done using the GraphPad Prism version 8.3.0.Results The most common age group operated upon in this study was the 40 to 60 years age group (n = 45, 39.48%). Males were 78% with male to female ratio of 3.56:1. The most common clinical presentation was altered sensorium (98.25%). The most common comorbidity was hypertension (n = 32, 28.07%). GCS at admission, severity of injury, pupillary changes, and best motor response (p < 0.0001) were significantly associated with surgical outcome.Conclusion GCS at admission, severity of injury, pupillary changes, and best motor response were significantly (p < 0.05) associated with surgical outcome. Age and gender of patients were not found to be significantly associated.
Keywords: Acute subdural hematoma; outcome predictive factors; operated acute SDH; Glasgow outcome score